COMPARISON BETWEEN PROPOFOL AND THIOPENTONE SODIUM FOR LARYNGEAL MASK AIRWAY INSERTION IN DAY CASE SURGERY - Khan, Parhaizgar; Afridi, Yasmeen (Journal of Postgraduate Medical Institute, 2011)
Objective: To assess the effectiveness of laryngeal mask airway insertion after induction with propofol or thiopentone in one hundred urological patients. Material and Methods: This study was carried out in the Department of Anaesthesiology Khyber Teaching Hospital Peshawar from January 2007 to June 2007. Hundred urological patients coming for day case surgery were included in the study. Patients were divided in to two groups (A & B) of fifty each. Group A (Propofol Group) received propofol (2.5mg/kg) and Group B (Thiopentone group) received thiopentone sodium (4-6 mg/kg) IV. Management of anaesthesia was identical in both groups. Midazolam 0.03 mg/kg body weight was used for co-induction. Laryngeal mask airway was inserted after adequate level of anaesthesia. The presence of gagging, coughing, laryngospasm and movement was noted and graded. Results: Thiopentone was associated with an adverse response in 76% of patients, compared with propofol in 26% (p<0.01). Head movement, laryngospasm, inadequate jaw relaxation were more common using thiopentone (p<0.05). The quality of anaesthesia according to patients was significantly higher in the propofol group (Group A, 80%) than in thiopentone group (Group B, 30%). Conclusion: Adverse responses in propofol Group were less than thiopentone Group. Propofol, therefore is superior to thiopentone as an induction agent for laryngeal mask airway.